2018
DOI: 10.1186/s12872-018-0820-6
|View full text |Cite
|
Sign up to set email alerts
|

Post percutaneous coronary interventional adverse cardiovascular outcomes and bleeding events observed with prasugrel versus clopidogrel: direct comparison through a meta-analysis

Abstract: BackgroundDue to limitations associated with clopidogrel following percutaneous coronary intervention (PCI), other newer oral anti-platelet agents are being studied. We aimed to systematically carry out a direct comparison of outcomes observed with prasugrel versus clopidogrel following PCI.MethodsCommon online searched databases (The Cochrane library, EMBASE, MEDLINE and Google scholar) were used to retrieve relevant publications. Primary endpoints were the adverse cardiovascular outcomes. Secondary outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Although there are higher risks of GIB and non‐CABG major bleeding with third‐generation P2Y 12 inhibitors than clopidogrel, use of third‐generation P2Y 12 inhibitors were associated with significant reduction in the mortality risk and major adverse cardiac events as compared with clopidogrel in patients with ACS as shown in previous RCTs and meta‐analysis . A meta‐analysis including nine RCTs also showed that the effect of prasugrel in decreasing the risk of major adverse cardiac events outweighed the increased risk of bleeding .…”
Section: Discussionmentioning
confidence: 80%
“…Although there are higher risks of GIB and non‐CABG major bleeding with third‐generation P2Y 12 inhibitors than clopidogrel, use of third‐generation P2Y 12 inhibitors were associated with significant reduction in the mortality risk and major adverse cardiac events as compared with clopidogrel in patients with ACS as shown in previous RCTs and meta‐analysis . A meta‐analysis including nine RCTs also showed that the effect of prasugrel in decreasing the risk of major adverse cardiac events outweighed the increased risk of bleeding .…”
Section: Discussionmentioning
confidence: 80%
“…41 Prasugrel and ticagrelor, novel oral P2Y12 receptor inhibitors, can play a role in patients not sensitive to clopidogrel. 42,43 With the application of new devices and new P2Y12 receptor inhibitors in the clinic, the duration of DAPT can be shortened.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of metal stent frameworks, polymer coatings and released antiproliferation agents, DESs have reduced the incidence of thrombogenicity 41 . Prasugrel and ticagrelor, novel oral P2Y12 receptor inhibitors, can play a role in patients not sensitive to clopidogrel 42,43 . With the application of new devices and new P2Y12 receptor inhibitors in the clinic, the duration of DAPT can be shortened.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding, as the most common side effects of thirdgeneration oral P2Y 12 inhibitors, has been well evaluated in previous studies [5][6][7]. Dyspnea was another important side effect, which was commonly reported in thirdgeneration oral P2Y 12 inhibitors users.…”
Section: Introductionmentioning
confidence: 99%